Google assisted EFL reading instruction - Kızıl, Aysel Şahin (My University, 2013)
The use of Google as a search engine has been a commonplace practice both in and beyond the education; however, what is recently burgeoning is the use of Google applications as instructional tools in the field of language education. Among various applications, Google docs launched in 2007 seem to be promising aids that could be explored to create effective, efficient and engaging learning environments. Google docs, in essence, is a free, user friendly, web-based word processing, spreadsheet and presentation program that allow teachers to design internet based activities. This paper presents the results of a-12-week study which integrated Google docs into EFL reading instruction. The participants were beginner level students of English (n=32). Throughout the study, the students were provided with Google-assisted reading activities to support their in-class teaching and they were required to keep vocabulary logs through Google docs. At the end of the study, they were administered a post instruction perception questionnaire asking about their attitudes towards using Google docs language learning. Students’ perceptions of this experience are discussed in relation to the course design, and practical suggestions are provided for language teachers wishing to create engaging learning environments.
Bildiri - Yayımlanmış
Keywords: English as a foreign language (EFL); Language teaching; Reading instruction; Google docs